Enabling interactive safety and performance trade-offs in early airframe systems design - Jimeno Altelarrea, Sergio; Riaz, Atif; Guenov, Marin D.; Molina-Cristobal, Arturo (American Institute of Aeronautics and Astronautics (AIAA), 2020)
Presented is a novel interactive framework for incorporating both safety and performance analyses in early systems architecture design, thus allowing the study of possible trade-offs. Traditionally, a systems architecture is first defined by the architects and then passed to experts, who manually create artefacts such as Fault Tree Analysis (FTA) for safety assessment, or computational workflows, for performance assessment. The downside of this manual approach is that if the architect modifies the systems architecture, most of the process needs to be repeated, which is tedious and time consuming. This limits the exploration of the design space, with the associated risk of missing better architectures. To overcome this limitation, the proposed framework automates parts of the safety and performance analysis in the context of the Requirement, Functional, Logical, and Physical (RFLP) systems engineering paradigm. Safety analysis is carried out by automatic creation of FTA models from the functional and logical flow views. Regarding performance analysis, computational workflows are first automatically created from the logical flow view, and then executed for a set of flight conditions over the range of the mission in order to determine the most demanding condition. Finally, performance characteristics of the subsystems, such as weights, power offtakes, ram drag etc. are evaluated at the most demanding flight condition, which enables the architect to compare architectures at aircraft level. The framework is illustrated with a representative example involving the design of an environmental control system of a civil aircraft, where the safety and performance trade-off is conducted for multiple ECS architectures.